Hodnocení finanční situace podniku a návrhy na její zlepšení - Chvátal, Vojtěch (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Bakalářská práce se zabývá hodnocením finanční situace podniku PCH výroba a projekty s.r.o. a následně návrhy na její zlepšení. V práci budu vycházet z účetních výkazů v letech 2016-2020. Bakalářská práce je rozdělena na teoretickou a praktickou část. V teoretické části objasním základní pojmy z finanční analýzy, které následně použiji v praktické části ke konkrétním výpočtům podle reálných dat společnosti. V závěru práce budou popsány mé návrhy na zlepšení finanční situace v podniku.

The bachelor’s thesis deals with evaluation of the company’s financial situation and then proposals for it’s improvement. Bachelor’s thesis will be based on financial statements in the years 2016-2020 and it is divided into theoretical and practical parts. In the theoretical part I will be explaining the basic concepts of financial analysis, which I will then use in the practical part for specific calculations according to real company data. At the end of the thesis I will describe my proposals to improve the financial situation in the company.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: finanční analýza; rozvaha; rentabilita; likvidita; swot analýza; financial analysis; balance sheet; profitability; liquidity; swot analysis